A discussion and plans for remodeling the hydraulic lighting plant at Chapman, Kansas - Gibbon, C. T.; Simpson, Jay W. (My University, 1908)
Introduction: When a hydro-electric generating plant it to be designed and installed the problem must be taken up with the greatest possible tact and detailed consideration. The first item of importance which must be taken into consideration is the probable amount of power that can be sold and the competition which is to be met in the sale.
Citation: Gibbon, C. T. and Simpson, Jay W. A discussion and plans for remodeling the hydraulic lighting plant at Chapman, Kansas. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Kansas; Blueprints; Hydroelectricity; Engineering; Graduating theses; Senior theses; Theses